2013
DOI: 10.1155/2013/354725
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hearing Loss in Children following Bacterial Meningitis in a Tertiary Referral Hospital

Abstract: Objective. This study aimed to examine hearing function in children admitted with bacterial meningitis to determine the risk factors for sensorineural hearing loss. Setting. The study was conducted in the audiology unit and paediatric wards of Kenyatta National Hospital. Subjects and Methods. The study involved 83 children between the ages of six months and twelve years admitted with bacterial meningitis. The median age for the children examined was 14. On discharge they underwent hearing testing to evaluate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…In a study in Kenya [ 9 ] and many other African countries [ 10 14 ], it was observed that there was a high prevalence of sensorineural hearing loss amongst children treated for bacterial meningitis ( Table 1 ). Children living in developing countries who fail to get vaccinated are at a greater risk of developing hearing loss sequel to bacterial meningitis infection [ 15 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In a study in Kenya [ 9 ] and many other African countries [ 10 14 ], it was observed that there was a high prevalence of sensorineural hearing loss amongst children treated for bacterial meningitis ( Table 1 ). Children living in developing countries who fail to get vaccinated are at a greater risk of developing hearing loss sequel to bacterial meningitis infection [ 15 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In the same way, in the case of meningitis, the close anatomical relationship with the cranial cavity plays a key role. 12 In cases of postmeningitis bacterial deafness, cVEMPs were induced in 0% of ears, while the response rate was of 50% in the deafness of viral origin. In order to obtain a greater level of significance, these data require a greater sample.…”
Section: Discussionmentioning
confidence: 98%
“…For the division into subgroups we relied on previous studies in the literature. [12][13][14][15][16] In the cases of HL due to a bacterial-viral cause, it is easier to find a concurrent vestibular disorder to a cochlear deficit, because of the close anatomical relationship that occurs between the two organs and the similarity of the receptor cells inside them. In the same way, in the case of meningitis, the close anatomical relationship with the cranial cavity plays a key role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Among a cohort of meningitic children in Kenya, 43.4% presented with SNHL post meningitis, of whom 61% had mild to moderate hearing loss and 38.7% severe to profound loss. [13] …”
Section: Hearing Function and Neurological Disordersmentioning
confidence: 99%